Best proximity point theorems: unriddling a special nonlinear programming problem - Sadiq Basha, S. (TOP, 2014)
This paper addresses the non-linear programming problem of globally minimizing the real valued function x ⟶ d ( x , Sx ) where S is a generalized proximal contraction in the setting of a metric space. Eventually, one can obtain optimal approximate solutions to some fixed-point equations in the event that they have no solution.